PENGGUNAAN MODEL PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS III SEKOLAH DASAR - Fauzatul Ma'rufah Rohmanurmeta; Erma Vismayanti; Novita Dwi Puspitaningrum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Students at elementary school age must be equipped with skills, not just focusing on knowledge. However, learning in schools is still rarely carried out by hands-on practical activities. Even though practical activities will have an impact on learning outcomes. This study aims to describe the increase in learning outcomes of students through the application of project-based learning in Indonesian subjects in class III SDN 02 Pandean. This type of research is classroom action research. Data collection techniques by way of observation, interviews, and tests. The results of this research show that the average learning outcomes of students in pre cycle was 66.55, cycle I was 80.69, and cycle II was 85.17 in the good category. The percentage of students' learning completeness increased from 58.62% to 86.21%. Thus, the application of the project-based learning (PjBL) model can improve the learning outcomes of students in Indonesian learning in class III SDN 02 Pandean.